Fitness equipment - CUCCIA, DARIO; KIESER RALF; SQUILLANTE ANTONIO (2022)
An exercise apparatus includes a base assembly, a table coupled to the base assembly, and a foot restraint coupled to the base assembly. The foot restraint is configured to apply resistance to at least one of one or more feet and one or more ankles of a user positioned in the fitness apparatus in response to a change in a relative position of the foot restraint with respect to the table. The fitness apparatus may also include a controller configured to at least one of (i) adjust a height of the table with one or more height actuators of the fitness apparatus, and (ii) adjust a rotation of the table with one or more rotation actuators of the fitness apparatus. 一种健身设备包括底座组件、耦合到底座组件的工作台，以及耦合到底座组件的脚部约束器。脚部约束器被配置为响应于脚部约束器相对于工作台的相对位置的改变而向定位在健身设备中的用户的一只或多只脚和一个或多个脚踝中的至少一者施加阻力。健身设备还可以包括控制器，该控制器被配置为以下至少一者：(i)利用健身设备的一个或多个高度致动器调整工作台的高度，和(ii)利用健身设备的一个或多个旋转致动器来调整工作台的旋转。